Consumer perceptions of internet retail service quality - Arshad, Noor Habibah; Janom, Norjansalika; Mohd Idris, Isnainy (2005)
Service quality is increasingly recognized as an important aspect of electronic commerce (e-commerce).Because the online comparison of the technical features of products is essentially costless, feasible and easier than comparisons of products through traditional channels, service quality is the key determinant for successful e-commerce.The purpose of this study is to explore consumers’ perceptions of Internet retail service quality.A number of dimensions have been described in the literatures, however six dimensions that are important to consumers in their assessment of the quality of Internet retailers were identified.These are reliability (how well an online retailer does in terms of meeting expectations regarding order fulfilment), access (Internet retailer’s ability to provide communication access and a variety of products from anywhere in the world), security (relating to perceptions of trust in the online retailer’s integrity regarding financial and privacy issues), efficiency (refers to the speed of search and downloading and prompt reply to enquiries), ease of use (how easy the Internet retailer’s website is for consumers to conduct, search and navigate) and information (quantity and credibility of information provider by the online retailer).Other objective is to highlight how online retailers can use the information from this study to enhance their service quality.Findings from the study could be used as the basis for the development of e-service quality for Internet retailing.